Sphingosine-1-phosphate and estrogen signaling in breast cancer. (January 2016) - Maczis, Melissa; Milstien, Sheldon; Spiegel, Sarah
Abstract: Breast cancer remains the most common malignant disease in women. The estrogen receptor-α (ERα) and its ligand 17β-estradiol (E2 ) play important roles in breast cancer. E2 elicits cellular effects by binding to ERα in the cytosol followed by receptor dimerization and translocation to the nucleus where it regulates gene expression by binding to ERE response elements. However, it has become apparent that E2 also exerts rapid non-genomic effects through membrane-associated receptors. There is emerging evidence that this induces formation of the bioactive sphingolipid metabolite sphingosine-1-phosphate (S1P). S1P in turn has been implicated in many processes important in breast cancer progression. One of the enzymes that produce S1P, sphingosine kinase 1 (SphK1), is upregulated in breast cancer and its expression has been correlated with poor prognosis. This review is focused on the role of the SphK/S1P axis in estrogen signaling and breast cancer progression and will discuss new therapeutic approaches targeting this axis for breast cancer treatment.